2011
DOI: 10.1557/jmr.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer on the metallic atom-pair bond and the bond energy

Abstract: Following our recent report demonstrating the significance of the nearest-neighbor unlike atom-pair bond in metallic alloys, an equation for the energy of such a bond is presented in this study. The success of empirically derived Miedema's equation in predicting the signs of the heats of formation of metallic alloys is explained. The negative contribution to the energy stems from the ionicity in the bond. The charge transfer on the bond, suggested by Pauling to establish electroneutrality, contributes the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…With c as electronegativity, obtained by normalizing Miedema's electronegativity F to Pauling's scale, and N as the metallic valence of elements [25] and identifying N 1 3 as electron density of an element on a bond, (called bond valence), an expression for the A-B bond energy was derived as…”
Section: Atom-pair Bond (Apb) Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…With c as electronegativity, obtained by normalizing Miedema's electronegativity F to Pauling's scale, and N as the metallic valence of elements [25] and identifying N 1 3 as electron density of an element on a bond, (called bond valence), an expression for the A-B bond energy was derived as…”
Section: Atom-pair Bond (Apb) Approachmentioning
confidence: 99%
“…Here, k, which has the dimensions of energy, is equal to zero, for compounds without p elements; and k takes values up to a maximum of 0.5 eV, depending on the valence of the p element in the compound [25].…”
Section: Atom-pair Bond (Apb) Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Miedema's electron density [28] represents values at the Wigner-Seitz cell boundary N ws rather than the outer number of electrons beyond the inert gas configuration. It has been shown that N ws represents the valence electron concentration per atom (N) of a metal elsewhere [29]. Further, it was demonstrated that the lattice parameters of the cubic L1 2 type compounds can be accurately predicted from just a knowledge of the elemental radii [2].…”
Section: Selection Of Fundamental Parameters To Examine Correlations ...mentioning
confidence: 99%
“…It was earlier reported that using Miedema's parameters [1,2], concomitant and mutually exclusive crystal structure types in metallic binary systems can be predicted with excellent accuracy [3][4][5][6][7][8]. It was shown that the metallic bond in intermetallic compounds is local in nature [6].…”
Section: Introduction 1motivationmentioning
confidence: 99%